Nonequilibrium quantum evolution of open systems - Sang Pyo, Kim (Condensed Matter Physics, 2000)
We apply the Liouville-von Neumann (LvN) approach to open systems to describe the nonequilibrium quantum evolution. The Liouville-von Neumann approach is a unified method that can be applied to both time-independent (closed) and time-dependent (open) systems and to both equilibrium and nonequilibrium systems. We study the nonequilibrium quantum evolution of oscillator models for open boson and fermion systems